Measuring atmospheric ion bursts and their dynamics using mass spectrometry - Junninen, Heikki; Duplissy, Jonathan; Ehn, Mikael; Sipilä, Mikko; Kangasluoma, Juha; Franchin, Alessandro; Petäjä, Tuukka; Manninen, Hanna E.; Kerminen, Veli-Matti; Worsnop, Douglas; Kulmala, Markku (Finnish Environment Institute, 2016)
Atmospheric ions are produced after a cascade of reactions starting from initial ionization by high energetic radiation. Such ionization bursts generate ions that rapidly react and generate a suite of ion products. Primary ions are in the atmosphere originate from radioactive decay, gamma radiation from the soil or cosmic ray events. In this work, we modified an existing instrumentation and developed a novel setup for detecting ion bursts. The setup consists of a continuous flow ionization chamber coupled to Atmospheric Pressure interface Time-Of-Flight (APi-TOF) mass spectrometer. The APi-TOF sampling rate was set to 100 Hz in order to detect individual ion bursts from ionization events. Besides counting the individual ionization events, the developed setup is able to follow the rapidly changing chemical composition of ions during ion burst cascade. The setup can give us insights into the primary ionization mechanisms and their importance in atmospheric ion and aerosol dynamics. Peer reviewed